To the origin of vibrational models in Raman spectra of Li₂B₄O₇ single crystals - Burak, Ya.V.; Adamin, V.T.; Teslyuk, I.M. (Functional Materials, 2006)
The Raman spectra investigations have been reported at room temperature in the 100-1200 cm⁻¹ range for Li₂B₄O₇ single crystals with natural Li and B isotopic distribution and for 4 types of single crystals enriched maximally in ⁷Li, ⁶Li, ¹⁰B and ¹¹B isotopes. It has been found that in spectra of Li₂B₄O₇ single crystals with natural isotopic distribution, no isotopic splitting takes place; this fact confirms the essentially single-mode behavior of those crystals. The specific modes are subdivided into 5 groups according to their frequency changes: (1) "regular" modes, where the frequency increases at decreasing isotope atomic mass, and vice versa; (2) modes, where the frequency remains insensitive to substitution of isotope; (3) the modes with anomalous behavior, where the frequency decreases at decreasing isotope mass, and vice versa; (4) the modes with frequency changing chaotically at substitution of isotopes; (5) "random" modes observed only in some samples. The origin of the vibrational modes in the Raman spectra of Li₂B₄O₇ single crystals is defined in more detail.